Training programme in gasless laparoscopy for rural surgeons of India (TARGET study) - Observational feasibility study. (September 2021) - Aruparayil, N.; Gnanaraj, J.; Maiti, S.; Chauhan, M.; Quyn, A.; Mishra, A.; Bains, L.; Mathew, G.; Harris, C.; Cundill, B.; Fellows, A.; Gordon, K.; et al.
Abstract: Background: Benefits of laparoscopic surgery are well recognised but uptake in rural settings of low- and middle-income countries is limited due to implementation barriers. Gasless laparoscopy has been proposed as an alternative but requires a trained rural surgical workforce to upscale. This study evaluates a feasibility of implementing a structured laparoscopic training programme for rural surgeons of North-East India. Methods: A 3-day training programme was held at Kolkata Medical College in March 2019. Laparoscopic knowledge and Fundamentals of Laparoscopic Skills (FLS) were assessed pre and post simulation training using multiple choice questions and the McGill Inanimate System for Training and Evaluation of Laparoscopic Skills (MISTELS), respectively. Competency with an abdominal lift device was assessed using the Objective Structured Assessment of Technical Skills (OSATS) and live operating performance via the Global Operative Assessment of Laparoscopic Skills (GOALS) scores during live surgery. Costs of the training programme and qualitative feedback were evaluated. Results: Seven rural surgeons participated. There was an improvement in knowledge acquisition (mean difference in MCQ score 5.57 (SD = 4.47)). The overall normalised mean MISTELS score for the FLS tasks improved from 386.02 (SD 110.52) pre-to 524.40 (SD 94.98) post-training (p = 0.09). Mean OSATS score was 22.4 out of 35 (SD 3.31) indicating competency with the abdominal lift device whilst a mean GOALS score of 16.42 out of 25 (SD 2.07) indicates proficiency in performing diagnostic laparoscopy using the gasless technique during live operating. Costs of the course were estimated at 354 USD for trainees and 461 USD for trainers. Conclusion: Structured training programme in gasless laparoscopy improves overall knowledge and skills acquisition in laparoscopic surgery for rural surgeons of North-East India. It is feasible to deliver a training programme in gasless laparoscopy for rural surgeons. Larger studies are needed to assess the benefits for wider adoption in a similar context. Highlights: Structured training in gasless laparoscopy is feasible for rural surgeons. Demonstrates overall improvement in knowledge and skill acquisition. The training environment is an essential component for rural surgeons. Lower costs support wider adoption in LMIC.